The Evolutionary Characteristics of Reservoir Microstructure under Long-Term Waterflooding Development and Its Fractal Description - Fengjiao Wang; Xu Wang; Yikun Liu; Qingjun Deng; Jianjun Xu; Yong Zhang; Huaiyuan Li (Geofluids)
Generally, long-term waterflooding development often leads to the change of reservoir pore and clay mineral composition, which results in the change of permeability and wettability. In order to explore the relationship between core micropore structure and water cut, based on physical simulation experiments and fractal theory, we proposed a fractal evolutionary model to describe the evolution characteristics of microstructure of long-term water driving reservoirs. In this paper, core pore structure by SEM was first conducted to analyze the change of core pore structure before and after waterflooding under the conditions of magnification of 200 times, 800 times, and 2000 times, respectively. Then, conventional and constant rate mercury injection tests were combined to perform the comparative analysis of core structural parameters before and after waterflooding. Finally, a micropore-throat structure evolution model of core was established. Research shows that the connectivity of larger pores becomes better after long-term water driving, the degree of heterogeneity weakens, and the micro heterogeneity of small pores becomes stronger and stronger. The throat characteristics change in a complex manner, the radius tends to increase, and the sorting becomes better, while the connectivity of small throat changes complex. In general, the heterogeneity of throat increases with the time of water injection in reservoirs with low porosity and permeability. On the basis of fractal theory and variation characteristics of rock pore structure in water driving reservoirs, we have established a micropore-throat structure evolution model of core pore-throat characteristics. This fractal evolution model quantitatively characterized the complexity and evolution law of pore structure and clarified the relationship between fractal dimension of core pore structure and water cut under different stages of water driving.